ANALISIS STRUKTUR YANG TERKANDUNG DALAM CERPEN UMAH - Ni Luh Putu Nitahapsari Rahayu (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2019)
Literary works are creations communicated expressively about the author`s intent for aesthetic purposes.. This study examines the intrinsic contained in the short story of Bali language entitled “umah” generally have opinions and different interpretation of a short story. The intrinsic element is all the outside elements that underlies and creation of literary works. The method used in this research descriptive research using descriptive research method. Method is a methodthe status of a human group, an object, a set of conditions, a system ofthought, or a classof events in the present. In the analysis of the short stories in Bali language, the work of this I Dewa Ketut Raka Kusuma, contains many moral values and social value that can be taken and learned by the readers.